2021
DOI: 10.3390/su13147631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Teacher Training in Systems Thinking on Biology Students—An Intervention Study

Abstract: Systems thinking provides many advantages in solving complex scientific, economic and sociocultural problems in the field of education for sustainable development. Various studies have shown that systems thinking can be promoted in students at all levels of school education. Previous studies have mainly focused on how to directly develop and support systems thinking in students. The present study focused on biology teachers by investigating the extent that their content knowledge (CK) and pedagogical content k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…The overwhelming majority of authors suggested only methods and procedures that are compatible with the constructivist learning paradigm for promoting comprehensive ESD goals [31]. In this view, self-regulated and self-directed learning of applicable knowledge and problem-solving skills are assigned a central role [32].…”
Section: Resultsmentioning
confidence: 99%
“…The overwhelming majority of authors suggested only methods and procedures that are compatible with the constructivist learning paradigm for promoting comprehensive ESD goals [31]. In this view, self-regulated and self-directed learning of applicable knowledge and problem-solving skills are assigned a central role [32].…”
Section: Resultsmentioning
confidence: 99%
“…However, very different aspects of modeling have been emphasized in the systems thinking literature: Various frameworks explicitly include modeling as a systems thinking skill, which, however, can describe different skills. For example, modeling can involve inferring statements about future system states but also understanding and/or creating system models (e.g., Sommer and Lücken, 2010;Mehren et al, 2018;Gilissen et al, 2020;Mambrey et al, 2020;Streiling et al, 2021). From a different perspective, models are viewed as representations of complex systems (Streiling et al, 2021;Kiesewetter and Schmiemann, 2022;Mambrey et al, 2022b).…”
Section: Modeling In Systems Thinking Researchmentioning
confidence: 99%
“…For example, modeling can involve inferring statements about future system states but also understanding and/or creating system models (e.g., Sommer and Lücken, 2010;Mehren et al, 2018;Gilissen et al, 2020;Mambrey et al, 2020;Streiling et al, 2021). From a different perspective, models are viewed as representations of complex systems (Streiling et al, 2021;Kiesewetter and Schmiemann, 2022;Mambrey et al, 2022b). In addition, they are the starting point for developing predictions (Gilissen et al, 2020).…”
Section: Modeling In Systems Thinking Researchmentioning
confidence: 99%
“…TCs were questioned regarding their use of project materials and curricula, their involvement in the Design and Innovation camps, their participation in the Becoming Changemaker coursework, their perceptions of the project's successes and challenges, and their perceptions of their own and their potential students' outcomes. [12] and consists of 11 items which prompted participants to rate their confidence in their teaching skills based on a series of statements on a Likert scale from 1(strongly disagree) to 5(strongly agree). One item on each scale was reverse coded.…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…Research suggests that using a systems perspective in teacher preparation can facilitate the formation of a teacher identity and improve TC capacity for developing solutions to problems that arise in the context of their own practice [4]. Other studies demonstrate effective strategies for enhancing TCs' capacity for systems thinking in environmental science [5], engineering education [6], and biology [7].…”
Section: Conceptual Frameworkmentioning
confidence: 99%